Organic chemistry : a modern approach - Hopkins, Francesca (United States : Murphy & Moore Publishing, 2022)
The branch of chemistry which deals with the reactions, properties, and structures of compounds in which carbon is present in covalent bonding is termed as organic chemistry. It involves the evaluation of chemical reactivity, physical properties and chemical composition of various organic compounds. These compounds are further classified into aromatic compounds, polymers, biomolecules, fullerenes, aliphatic compounds and heterocyclic compounds. Some of the common analytical methods studied under the discipline of organic chemistry are elemental analysis, nuclear magnetic resonance spectroscopy, crystallography and mass spectrometry. It finds extensive applications in the fields of pharmaceuticals, agrichemicals and petrochemicals, consumer products, biotechnology and chemical engineering. This book includes some of the vital pieces of work being conducted across the world, on various topics related to organic chemistry. The various sub-fields of organic chemistry along with technological progress that have future implications are glanced at herein. This book is a vital tool for all researching and studying this field.
Includes index.
Includes bibliographical references.
Keywords: Organic Chemistry